Perbandingan Daya Dukung Pondasi Tiang Pancang Menggunakan Data Sondir Dan SPT Dengan Menggunakan Metode Elemen Hingga Pada Pembangunan Sekolah Teologi Anugerah Misi Kabupaten Nias Barat - Andrey Muhammad Nasution; Darlina Tanjung; Jupriah Sarifah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The foundation is a substructure which functions to support the loads and forces caused by the superstructure (superstructure) to the soil layer which will carry these loads and forces. Deep foundations are usually used to obtain a large enough soil bearing capacity and if the depth of the hard soil is far below the ground surface. The aim of this task is to analyze the bearing capacity of pile foundations using sondir data, standard penetration test (SPT) data, as well as the finite element method using the plaxis program. The method used in this final assignment is by studying literature, then collecting the necessary data, and after that carrying out calculation analysis using existing methods. From the results of the calculations carried out, different results were obtained. Where for sondir data at point S1 obtained Qu =115.80 tons; at point S2 obtained Qu = 104.80 tons; at point S3 obtained Qu = 105.50 tons. Meanwhile, based on SPT data at point BH-01, Qu = 398.23 tons, and using the plaxis program Qu = 425 tons